The Three-Dimensional Microenvironment of the Mitral Valve: Insights into the Effects of Physiological Loads - Ayoub, Salma (Cell Mol Bioeng, 2018)
INTRODUCTION: In the mitral valve (MV), numerous pathological factors, especially those resulting from changes in external loading, have been shown to affect MV structure and composition. Such changes are driven by the MV interstitial cell (MVIC) population via protein synthesis and enzymatic degradation of extracellular matrix (ECM) components. METHODS: While cell phenotype, ECM composition and regulation, and tissue level changes in MVIC shape under stress have been studied, a detailed understanding of the three-dimensional (3D) microstructural mechanisms are lacking. As a first step in addressing this challenge, we applied focused ion beam scanning electron microscopy (FIB-SEM) to reveal novel details of the MV microenvironment in 3D. RESULTS: We demonstrated that collagen is organized into large fibers consisting of an average of 605 ± 113 fibrils, with a mean diameter of 61.2 ± 9.8 nm. In contrast, elastin was organized into two distinct structural subtypes: (1) sheet-like lamellar elastin, and (2) circumferentially oriented elastin struts, based on both the aspect ratio and transmural tilt. MVICs were observed to have a large cytoplasmic volume, as evidenced by the large mean surface area to volume ratio 3.68 ± 0.35, which increased under physiological loading conditions to 4.98 ± 1.17. CONCLUSIONS: Our findings suggest that each MVIC mechanically interacted only with the nearest 3–4 collagen fibers. This key observation suggests that in developing multiscale MV models, each MVIC can be considered a mechanically integral part of the local fiber ensemble and is unlikely to be influenced by more distant structures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12195-018-0529-8) contains supplementary material, which is available to authorized users.